Peran Non Performing Asset, Capital Adequacy dan Insolvency Risk Terhadap Kinerja Bank - Nabila Anjani; H Hersugondo (JURNAL STUDI MANAJEMEN ORGANISASI, 2020)
The purpose of this study is to examine whether Non Performing Asset, Capital Adequacy, and Insolvency Risk can affect bank performance. This study use size and age of bank as control variables. The data that used in this study are secondary data obtained from the annual banking financial statements dor state-owned commercial banks and private commercial banks operated in Indonesia from 2014 to 2018. Panel data regression is used to analyzed the hypothesis that has been determined for this study.The result of the study is Non Performing Asset that used the ratio of Gross NPA and Net NPA as the measurement indicators have significant and negative relationship to bank performance using ROA as the indicators. A significant negative relationship was also found in the relationship of Capital Adequacy and bank performance. Insolvency Risk determined by Z-Score indicates that the banks in this study included as safe area category which referred to a healthy bank so it has a significant relationship to bank performance.